A PROHORMONE OF OUR ORGANISM - Sh. D. Mamarova; R. Y. Inatullaeva; U. U. Sotiboldieva; J.K. Kodirjanov (Western European Studies, 2026)
Vitamin D possesses both vitamin and hormone properties, with its primary function being the regulation of calcium-phosphorus metabolism and the maintenance of bone strength. Recent studies demonstrate its significant role in the immune system, endocrine and cardiovascular processes, as well as in the regulation of glucose metabolism. Vitamin D deficiency is recognized as a global public health issue, mainly caused by limited sun exposure, unbalanced diet, and chronic diseases. Deficiency leads to impaired bone mineralization and increases the risk of autoimmune, cardiovascular, and metabolic disorders. The article presents information on the functions of vitamin D, its sources, risk factors for deficiency, and preventive measures.
Keywords: vitamin D; calcium-phosphorus metabolism; bone health